2020
DOI: 10.1002/aoc.5379
|View full text |Cite
|
Sign up to set email alerts
|

NHC‐assisted Ni(II)‐catalyzed acceptorless dehydrogenation of amines and secondary alcohols

Abstract: A novel catalytic system including NiCl2‐NHC ligand precursor has been developed for the preparation of imines from amines and ketones from alcohols. Owing to the acceptorless dehydrogenation pathway for this reaction, the hydrogen gas is liberated as a by‐product. The active catalyst is generated in situ by the reaction of nickel (II) chloride, bis (imidazolium) chlorides and potassium tert‐butoxide. The products were obtained in good to excellent yields and a wide variety of amines and ketones were applied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The obtained aldimine forms the corresponding imine by subjecting it to a condensation reaction with RNH 2 ( Scheme 3 ). 54 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained aldimine forms the corresponding imine by subjecting it to a condensation reaction with RNH 2 ( Scheme 3 ). 54 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 4 , Takallou and co-workers reported the Ni-catalyzed the preparation of imines from amines (eqn (1)). 54 In 2019, Co-catalyzed dehydrogenative coupling of amines into imines (eqn (2)). 55 This comparison shows that using mesoporous PGTSA/Ni system lead to synthesis products in higher yields times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] In another study, Takallou and co-workers reported a new in situ generated Ni-NHC catalyst for preparation of a wide range of homo-and hetero-coupled imine products by employing amines as HCOCs. [36] Moreover, this catalytic system was applied for the synthesis of ketones starting from secondary Scheme 17. N-Alkylation of different aromatic amines with alcohols catalyzed by complex 25. alcohol.…”
Section: K 2 -Coordinated Nhc Ligandsmentioning
confidence: 99%